Gender equality in top managerial positions in a South African Mining Company - Takadi, Kutlwano Gwendoline (University of the Free State, 2021)
Mining has been inextricably intertwined with South Africa's political economy since the advent of large-scale and profitable mining in the 1860s. A keen study of the production and trade dynamics of the mining sector and their relations with the law, social norms and government policies and regulations, and how these have contributed to and impacted the distribution of national income and wealth, and their attendant dynamics, has been a reliable bellwether of the socio-economic vibrancy of the South African Republic through successive historical epochs. A key issue through these successive epochs has been labour issues generally and the participation of women in the mining sector labour force specifically. Against this backdrop, the research reported in this dissertation had the primary objective of examining gender equality in top managerial positions in the South African mining company, Anglo American. The secondary objectives included an exploration of gender-related causes of women's non-progression to senior leadership positions; the determination of gender-related personal values among occupants of top and senior management positions in the company; and the development of a framework to reduce gender disparities within top and senior management at Anglo American. To seek answers to these objectives, the research deployed a cross-sectional survey design within a transformative research paradigm. The research established that, although Anglo American has made considerable progress in ensuring gender parity within top and senior management positions and is generally performing well above the industry average, still more needs to be done to comply with the applicable legislative and policy instruments. In distilling the insights from the research, the study formulated a framework through which the company can achieve the required gender parity at top and senior management positions.
Dissertation (MBA (Business Administration))--University of the Free State, 2021
Keywords: Mining; gender equality; South African mining company; top managerial positions; women in mining; gender differences; women; women progression in mining; challenges of women in mining; Anglo American